Simultaneous Catalytic Removal of VOCs and NOx with the Dual-layered Catalyst of CoCeOx and V2O5/TiO2 - Yujie Fu; Qi Xin; Shuo Zhang; Yang Yang (Aerosol and Air Quality Research)
Abstract NO and volatile organic compounds (VOCs) are ones of exhaust with high irritation and toxicity, thus it is very necessary to develop a catalyst that can simultaneously remove them. In this study, a type of dual-layered catalyst has been prepared by combining CoCeOx and V2O5/TiO2 as different functional layers. The dual-layered catalyst was tested under NO, NH3, propane and the mixing atmosphere, achieving great NOx removal efficiency and good propane degradation under wide range temperature window. It is presented that NO conversion could reach 100% at 225°C and kept more than 80% at 175−300°C, while VOCs degradation reached 80% above 260°C. Moreover, the dual-layered catalyst with different construction is surveyed to reveal the mechanism included in this special construction. It is supposed that V2O5/TiO2 layer possesses rich acid sites which adsorbs NH3 as an ammonia buffer part and CoCeOx layer provides good oxidizing ability to oxidize NO and propane. The combination moderates the competitive adsorption between NH3 and propane which is the initial obstacle for multiple pollutants removal.